Membudayakan Alam berdasarkan perintah Allah dan Implementasinya bagi masyarakat Desa Hoyane - Abram2 Tondong2 (IAKN Ambon, 2023)
Indonesia is one of the countries that is the lungs of the world. This nation has extraordinary environmental potential, in the form of natural resource conditions, demographic conditions and geographical conditions that are not shared by other countries. Managing nature is something that has become a tradition and has also become an identity in an area, especially the Hoyane village community which is the object of research where the Hoyane people have a habit of opening new land every year for field rice planting, resulting in land degradation. Soil is very important and beneficial for human life. One of the important functions of soil is to store water reserves. Humans, who are God's glorious creations, clearly have a considerable influence on the environment, both directly and indirectly. Humans who are given the mandate to manage nature see it as an object that can be exploited to meet human needs. So in this way humans manage nature without looking at the potential for natural damage. Christianity believes that God gave nature for humans to manage and preserve. Wrong understanding often leads to wrong behavior in the use of nature, Christianity needs to provide a preventive view, as well as a repressive view of how human behavior should be towards nature. It is hoped that this paper will provide enlightenment and provide a new understanding of the environment in which we live and respect nature, because any human being, whether from students or uneducated, from rich or poor, from children or adults, certainly has the potential to destroy nature. and even become a source of problems for the natural environment. It is from this fact that the authors are interested in examining it using descriptive qualitative methods to provide education for the community.